Fundamentals of applied econometrics - Ashley, Richard A. [ (Richard Arthur)] , 1950- (Wiley, 2012)
"Fundamentals of Applied Econometrics is designed for an applied, undergraduate econometrics course providing students with an understanding of the most fundamental econometric ideas and tools. The texts serves both the student whose interest is in understanding how one can use sample data to illuminate economic theory and the student who wants and needs a solid intellectual foundation on which to build practical experiential expertise. Starting with a unique Statistics review to start the book, students will learn by doing. Ashley provides students with integrated, hands-on exercises, and the text is supplemented with Active Learning Exercises"